Pengaruh Implementasi Model Pembelajaran Inkuiri Terbimbing (Guided Inquiry) Berbantuan Video Pembelajaran Terhadap Hasil Belajar Siswa Kelas Xi SMA Pada Materi Trmokimia - Tamba, Nancy Davici; Bajoka Nainggolan (ARKA INSTITUTE, 2022)
This research was conducted to analyze the effect of the implementation of Guided Inquiry and Direct Instruction learning models assisted by learning videos. The learning outcomes of students taught by the guided inquiry were higher than those taught by Direct Instruction. This research was carried out at SMA Negeri 1 Ronggurnihuta, Samosir Regency. This research is quasi-experimental research (Quasi-Experimental Design), which consists of an experimental class with a Guided Inquired learning model and a control class with Direct Instruction. The data is processed descriptively and quantitatively analyzed using the SPSS 20 for the windows program. 34.17, and the average value of the Posttest is 82.36. While in the control class, the average value of the pretest was 25.42, and the post-test value was 76.94. From the data processing and analysis, it was obtained that the experimental class learning outcomes with N-Gain increased by 74.28% (in the high category) and the control class with N-Gain by 69.81% (in the medium category). It can be concluded that the guided inquiry learning model assisted by video learning is better and more effective in improving student learning outcomes than the Direct Instruction model.